Executive function in depression: the role of performance strategies in aiding depressed and non-depressed participants. Issue 2 (1st February 1999) - Channon, S; Green, P S S
Abstract : OBJECTIVES: Depression has been found to be associated with dysfunction in executive processes, whereas relatively automatic processes are thought to remain intact. Failure to generate or implement adequate performance strategies has been postulated in depressed participants. The present study investigated spontaneous strategy usage in depressed and control participants, and the effectiveness of providing a hint about performance strategies. METHODS: Unipolar depressed participants were compared with matched healthy controls on three tasks sensitive to executive function: memory for categorised words, response suppression, and multiple scheduling. Participants in each group were randomly allocated to strategy aid and no strategy aid conditions. Those in the strategy aid condition were given a hint about the use of an appropriate performance strategy for each task, in addition to the standard instructions given to those in the no strategy aid condition. RESULTS: Depressed participants performed worse than controls on each of the three tasks, and were found to use appropriate performance strategies less often. Provision of strategy hints increased the use of performance strategies in two of the three tasks, memory for categorised words, and response suppression, but did not significantly improve overall performance for either group. CONCLUSIONS: The findings were consistent with the view that depressed participants fail to use appropriate performance strategies spontaneously to the same extent as controls. However, provision of information alone does not seem to be an adequate means of enhancing performance. The role of performance strategies in cognitive impairment in depression is discussed, both in terms of initiating use of such strategies and carrying these out efficiently.